Assessment of Respondents’ Accordance with Entrepreneurial Concepts and Personal Inclinations Towards Entrepreneurship - Mustafa, Mohd Ariff; Pauzi, Nur Farahah Mohd; Shamsudin, Adriana; Ahmad, Khairiah; Zazili, Ainol Sarina Ahmad; Jailani, Jalaluddin Mohamad (Advances in Social Sciences Research Journal, 2024)
The Malaysian government has implemented numerous initiatives to foster entrepreneurial endeavours among university graduates. The objective is to equip students with the essential knowledge, skills, and mindset required to establish prosperous and enduring enterprises. However, even with the implementation of many programmes, the rate of entrepreneurship among graduates remains low. Given the rising unemployment rate in the country, exacerbated by the challenging economic circumstances resulting from the pandemic, it is imperative to encourage entrepreneurial endeavours. The objective of this study is to assess students’ comprehension and receptiveness towards subjects related to entrepreneurship, considering the present circumstances. A cohort of 252 undergraduate students participated in the study by completing self-administered questionnaires. The findings demonstrated a notable and favourable correlation between persons’ self-evaluated proficiency and their inclination towards being interested in things linked to entrepreneurship. The purpose of this analysis is to offer valuable insights to universities to construct entrepreneurship programmes. The ultimate objective is to improve entrepreneurial education and establish a conducive atmosphere for students to discover and pursue entrepreneurial ideas.